2022
DOI: 10.3390/molecules27175470
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Stimulates the Terpenoid Backbone and Triterpenoid Biosynthesis Pathway to Promote the Synthesis of Saikosaponin in Bupleurum chinense DC. Roots

Abstract: Bupleurum chinense is an important medicinal plant in China; however, little is known regarding how this plant transcribes and synthesizes saikosaponins under drought stress. Herein, we investigated how drought stress stimulates the transcriptional changes of B. chinense to synthesize saikosaponins. Short-term drought stress induced the accumulation of saikosaponins, especially from the first re-watering stage (RD_1 stage) to the second re-watering stage (RD_2 stage). Saikosaponin-a and saikosaponin-d increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The biosynthesis of the terpenoid skeleton is responsible for the later formation of different terpenoids (Sun & Li, 2018 ). Bupleurum chinense promotes the synthesis of saikosaponin by affecting the terpene skeleton and triterpenoid biosynthesis (Yang et al, 2022 ). More investigation is needed to determine whether P. praeruptorum produces terpenes via rhizosphere fungi, thereby facilitating the production of saponins.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of the terpenoid skeleton is responsible for the later formation of different terpenoids (Sun & Li, 2018 ). Bupleurum chinense promotes the synthesis of saikosaponin by affecting the terpene skeleton and triterpenoid biosynthesis (Yang et al, 2022 ). More investigation is needed to determine whether P. praeruptorum produces terpenes via rhizosphere fungi, thereby facilitating the production of saponins.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the triterpenoid saponins, predominant types of licorice derived from glycyrrhizin, the classic oleanane structure, stemming from the mevalonic acid pathway of terpene backbone. Several investigations have suggested that triterpenoid saponins have been conducive to the adaptation of plants in water-deficit conditions [48][49][50]. Currently, the pathway of glycyrrhizin has been completely clarified, obtaining bAS, two key CYP450 enzymes (CYP88D6 and CYP72A154), and two UDPs (GuCSyGT and UGT73P12).…”
Section: Discussionmentioning
confidence: 99%
“…The tea saponin biosynthesis pathway can be divided into initiation, skeleton construction, and modification [9,10]. In the initial stage, isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) are synthesized via mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the biosynthesis pathway of tea saponin is still in its infancy, and the main task is to mine genomic and transcriptome data. For example, Yang et al [10] identified key genes in the tea saponin biosynthesis pathway, including 143 key genes in the initial and skeleton construction stage and 1169 CYP450 and 1019 UGT in the modification phase, by analyzing the released genome data of C. oleifera [12]. Yang et al [13] cloned 41 WRKY transcription factors through transcriptome sequencing, five of which may regulate SQS genes, and proved that CoWRKY1 could bind to the promoter region of SQS by using yeast monohybrid (Y1H) technology.…”
Section: Introductionmentioning
confidence: 99%